Differential Diagnostic Models Between Vasovagal Syncope and Psychogenic Pseudosyncope in Children - Zhang, Zhening; Jiang, Xingyuan; Han, Lu; Chen, Selena; Tao, Ling; Tao, Chunyan; Tian, Hong; Du, Junbao (Frontiers in Neurology, 2020)
Objective: We aimed to establish useful models for the clinical differential diagnosis between vasovagal syncope (VVS) and psychogenic pseudosyncope (PPS). Methods: This bicentric study included 176 patients (150 VVS and 26 PPS cases) for model development. Based on the results of univariate and multivariate analyses, a logistic regression model and a scoring model were established and their abilities to differentiate PPS from VVS were tested. Another 78 patients (53 VVS and 25 PPS) were used for external validation. Results: In the logistic regression model, the outcome indicated that the QT-dispersion (QTd) (P＜0.001), syncope duration (P＜0.001) and upright posture (P＜0.001) acted as independent factors for the differentiation of VVS from PPS, which generated an area under the curve (AUC) of 0.892. A cutoff value of 0.234 yielded a sensitivity and specificity of 89.3% and 80.8%, respectively, for the differentiation between VVS and PPS in the logistic regression model. In the scoring model which consists of 3 variables, a cutoff score of 3 points yielded a sensitivity and specificity of 91.3% and 76.9%, respectively, with an AUC of 0.909. The external validation test indicated that the negative and positive predictive values of the scoring model were 78.8% and 91.7%, respectively, and the accuracy was 80.8%. Conclusion: The scoring model consisting of 3 variables is an easy-to-perform, inexpensive and non-invasive measure for initial differential diagnosis between VVS and PPS.